Evaluation of the influence of bioceramic sealers on the radiopacity of single-cone fillings - Antonio Batista,; Lisa Yurie Oda,; Felipe Andretta Copelli,; Bruno Cavalini Cavenago,; André Luiz da Costa Michelotto,; Clarissa Teles Rodrigues, (Revista Sul-Brasileira de Odontologia, 2025)
Radiopacity is an essential physical property to measure the quality of the filling, and whether the association of bioceramic sealers with gutta-percha cones increases the radiopacity of the filling was not previously assessed. Material and methods: Sixty transparent resin blocks with simulated root canals were prepared and X-rayed with a gutta-percha cone. The blocks were divided into five groups and filled with the single-cone technique using AH Plus (Dentsply Sirona, Ballaigues, Switzerland), AH Plus Bioceramic (Dentsply Sirona, Ballaigues, Switzerland), Bio-C Sealer (Angelus, Londrina, Brazil), BioRoot RCS (Septodont, Saint Maur-des[1]Fosses, France), or Sealer Plus BC (MK Life, Porto Alegre, Brazil). New radiographs were taken, and the images were analyzed using the Adobe Photoshop software (Adobe Systems Inc., San Jose, USA). Results: There was no difference (p>0.05) in the radiopacity of the gutta-percha cones used in the five groups. The epoxy resin-based AH Plus and AH Plus Bioceramic showed the highest increase in radiopacity (p<0.05). Sealer Plus BC, BioRoot RCS, and Bio-C Sealer showed similar radiopacity y (p<0.05). Conclusion: All sealers showed increased radiopacity (p<0.05) when associated with the gutta-percha cone.